Human rhinovirus serotypes induces different immune responses - Ji Heui Kim (BMC, 2021)
Abstract Background Different species of human rhinovirus (HRV) can induce varied antiviral and inflammatory responses in human blood macrophages and lower airway epithelium. Although human nasal epithelial cells (HNECs) are a primary infection route of HRV, differences between major and minor groups of HRV in the upper airway epithelium have not been studied in detail. In this study, we investigated viral replications and immune responses of major and minor groups of HRV in the HNECs. Methods Viral replication, immune responses of IFN-β, IFN-λ, proinflammatory cytokines, and viral receptors, and mRNA expression of transcription factors of HRV16 (major group) and HRV1B (minor group) in the HNECs were assessed. Results Compared with HRV16, HRV1B replicated more actively without excessive cell death and produced higher IFN-β, IFN-λ1/3, CXCL10, IL-6, IL-8, and IL-18 levels. Furthermore, low-density lipoprotein receptor (LDLR), TLR3, MDA5, NF-κB, STAT1, and STAT2 mRNA levels increased in HRV1B-infected HNECs. Conclusion HRV1B induces a stronger antiviral and inflammatory response from cell entry to downstream signaling compared with HRV16.